Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1038/bjc.1998.661
|View full text |Cite
|
Sign up to set email alerts
|

Meat intake, 'mate' drinking and renal cell cancer in Uruguay: a case-control study

Abstract: SummaryIn the period January 1988-December 1995. a case-control study of diet and renal cell carcinoma (RCC) risk involving 121 cases and 243 hospitalized controls was carried out in Montevideo, Uruguay. After adjusting for major covariates, red meat intake was associated with a 3.4 increase in risk for the highest category of intake, with a significant dose-response pattem. Also, barbecued meat, protein and heterocyclic amine intakes were associated with significant increases in risk of RCC. The consumption o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 18 publications
(2 reference statements)
2
36
0
2
Order By: Relevance
“…Ecological studies have shown positive associations between per-capita consumption of fat and protein intake with kidney cancer mortality rates. 2,3 Case-control studies have also found positive associations between risk of renal cell carcinoma and a high intake of energy, [4][5][6][7][8][9] protein and fat, particularly from animal foods, 4,6,7,10 and negative associations with polyunsaturated fat intake. 11,12 However, the evidence from prospective studies is sparse and the World Cancer Research Fund concluded that there is no consistent support for any foods or nutrients with renal cell carcinoma risk.…”
mentioning
confidence: 99%
“…Ecological studies have shown positive associations between per-capita consumption of fat and protein intake with kidney cancer mortality rates. 2,3 Case-control studies have also found positive associations between risk of renal cell carcinoma and a high intake of energy, [4][5][6][7][8][9] protein and fat, particularly from animal foods, 4,6,7,10 and negative associations with polyunsaturated fat intake. 11,12 However, the evidence from prospective studies is sparse and the World Cancer Research Fund concluded that there is no consistent support for any foods or nutrients with renal cell carcinoma risk.…”
mentioning
confidence: 99%
“…The present study included twelve epidemiological studies (ten case-control (McLaughlin et al, 1984;Goodman et al, 1986;Talamini et al, 1990;Kreiger et al, 1993;Mellemgaard et al, 1994;De Stefani et al, 1998;Bianchi et al, 2000;Hu et al, 2009;Montella et al, 2009;Wang et al, 2012) and two cohort studies (Lee Table 1. Of the ten case-control studies, five were conducted in the USA/Canada (McLaughlin et al, 1984;Goodman et al, 1986;Kreiger et al, 1993;Bianchi et al, 2000;Hu et al, 2009), and the remaining five were conducted in Denmark (Mellemgaard et al, 1994), Italy (Montella et al, 2009), Uruguay (De Stefani et al, 1998), and China (Wang et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Of the ten case-control studies, five were conducted in the USA/Canada (McLaughlin et al, 1984;Goodman et al, 1986;Kreiger et al, 1993;Bianchi et al, 2000;Hu et al, 2009), and the remaining five were conducted in Denmark (Mellemgaard et al, 1994), Italy (Montella et al, 2009), Uruguay (De Stefani et al, 1998), and China (Wang et al, 2012). Of the two cohort studies, one was conducted in UK (Allen et al, 2011), and the other one was conducted in the USA (Lee et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations